دور القنوات التلفزيونية الاخبارية العربية (الجزيرة ) في ابراز وحشية الاحتلال الصهيوني على الشعب الصهيوني ( طوفان الاقصى ) - بلال العلمي بخاوة; حمني التخي; د/ ذهبية ايت قاسي (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: هدفت الدراسة الى دراسة دور القنوات التلفزيونية الإخبارية العربية (الجزيرة) في ابراز وحشية الاحتلال الصهيوني على الشعب الفلسطيني (طوفان الأقصى) من خلالالتعرض الى دور هذه القنوات الإخبارية على رسها قناة الجزيرة في تغطية الحرب على غزة دراسة ميدانية على طلبة جامعة عمار ثليجي بالأغواط، وانطلقت دراستنا من إشكالية ما دور القنوات التلفزيونيةالإخبارية العربية الجزيرة في إبرازوحشية الاحتلال الصهيوني على الشعب الفلسطيني من خلال (طوفان الأقصى)؟، كما تفرعت الى مجموعة من الأسئلة الفرعية: - ما مدى إقبال الجمهور على مشاهدة القنوات التلفزيونيةالإخبارية العربية (الجزيرة) في متابعة طوفان الأقصى؟ - هل هناك مصداقية في كل ما يعرض في القنوات التلفزيونيةالإخبارية العربية في تقصي أخبار الحرب على غزة من خلال " طوفان الأقصى"؟ - ما هي الاشباعات المحققة متابعة الحرب على عزة عبر القنوات التلفزيونيةالإخبارية العربية (الجزيرة) وما الاشباعات المحققة؟ وهدفت دراستنا بشكل عام الى التعرف دور القنوات التلفزيونيةالإخبارية العربية الجزيرة في إبرازوحشية الاحتلال الصهيوني على الشعب الفلسطيني من خلال (طوفان الأقصى)، وقد اعتمدنا في دراستنا على المنهج الوصفي التحليلي مع توظيف أداة الاستبيان على عينة بلغت 100 فردا وقد توصلت الدراسة الى: 1. هناك اعتماد كبير على القنوات الإخبارية (الجزيرة) في تقصي أخبار الحرب على غزة من خلال " طوفان الأقصى" 2. توجد مصداقية في كل ما يعرض في القنوات الإخبارية ( الجزيرة) في تقصي أخبار الحرب على غزة من خلال " طوفان الأقصى". الكلمات المفتاحية: القنوات الإخبارية، الحرب، غزة، طوفان الأقصى Study summary: The study aimed to study the role of the Arab television news channels (Al-Jazeera) in highlighting the brutality of the Zionist occupation against the Palestinian people (the Al-Aqsa flood) by examining the role of these news channels, led by Al-Jazeera, in covering the war on Gaza. A field study on the students of Ammar Theliji University in Laghouat. Our study started from the problem of: What is the role of the Arab news television channels Al-Jazeera in highlighting the brutality of the Zionist occupation on the Palestinian people through (Al-Aqsa Flood)? It also branched into a set of sub-questions: 1. To what extent is the public’s interest in watching Arab television news channels (Al Jazeera) following the Al-Aqsa flood? 2. Is there credibility in everything shown on Arab television news channels in investigating the news of the war on Gaza through the “Al-Aqsa Flood”? 3. What are the satisfactions achieved by following the war on Azza on Arab television news channels (Al Jazeera) and what are the satisfactions achieved? In general, our study aimed to identify the role of the Arab news television channels Al Jazeera in highlighting the brutality of the Zionist occupation on the Palestinian people through (Al-Aqsa Flood). In our study, we relied on the descriptive analytical approach, using a questionnaire tool on a sample of 100 individuals. The study concluded: 1. There is a heavy reliance on news channels (Al Jazeera) to investigate news of the war on Gaza through the “Al-Aqsa Flood.” 2. There is credibility in everything shown on the news channels (Al Jazeera) in investigating the news of the war on Gaza through the “Al-Aqsa Flood.” Keywords: news channels, war, Gaza, Al-Aqsa flood
دراسة ميدانية لدى عينة من طلبة جامعة عمار ثليجي بالاغواط